Directed energy deposition process development for functionally gradient Copper-Inconel 718 materials (Journal of Additive Manufacturing Technologies, 2021)
Bimetallic systems are widely used in applications requiring combination of different material properties, such as in the aerospace industry, nuclear industry. Especially in rocket propulsions, Copper-Inconel alloys provide significant advantages due to the excellent heat conduction and wear resistance of Copper alloy and corrosion and oxidation resistance of the Inconel alloy. However, bimetallic systems produced by traditional methods could fail because of different material behavior under extreme conditions. Recently, additive manufacturing (AM) is considered as a promising technique to produce functionally graded materials (FGM) for large and complex parts with a short lead-time. In this paper, we aim to develop a CuSn10-Inconel 718 functionally gradient material using directed energy deposition (DED) AM process to elucidate the relation between process parameters and the microstructure. The DED process parameters have been optimized to produce desired FGM structure, and thermodynamic calculations have been conducted to investigate undesired phases within the gradient structure. Microstructure and the elemental composition of the gradient material have been investigated using scanning electron microscopy (SEM) and energy dispersive spectroscopy (EDS). The study aims to combine the experimental and thermodynamic computational modeling, to demonstrate the viability of assessment through computational work for a gradient material additively manufactured by DED processes.
Keywords: Additive manufacturing; Thermodynamic computational modeling; Directed energy deposition; Microstructure